Biomonitoring by using Rapid-Read Pathogenic Bacteria Indicator in Sediments and Bivalve Mollusks: Southern Gulf of Thailand, a Mangrove Area Case Study - Nuangjui, Manudchaya; Pimpang, Burassakorn; Chulalaksananukul, Warawut; Glinwong, Chompunuch (Trends in Sciences, 2023)
Pathogenic bacteria groups can be applied to be rapid bioindicator for environmental assessment. The objective of study was to monitor 5 groups of indicator and pathogenic bacteria (Escherichia coli/ total coliform, Salmonella spp., Vibrio spp., Bacillus spp. and Clostridium spp.) in surface water sediments collected before monsoon and after monsoon season from 6 areas located in a Thepha District, Songkhla province mangrove closed to Southern gulf of Thailand. Each collected area were selected in criteria of totally different in environment parameter and tide. The relative levels of total coliforms, and E. coli, were typically increased in rainy season (July) compared with winter and summer at most sites. In parallel, the highest number of Vibrio spp. was found in summer (April). The highest number of E. coli and Coliform were detected during rainy season at the estuary area with low oxygen dissolved, the average numbers were 6.6×103 and 3.8×105 CFU/g, respectively. Coliform number shows negative correlate with dissolved oxygen (r2 = 0.756, p < 0.05). In addition, total coliform, Bacillus spp. and Clostridium spp. were found in bivalve mollusks during rainy season but the total was not over standard. A very strong positive correlation was found between the temperature and the number of Vibrio spp. and Bacillus spp. The number presence of Vibrio spp. has a strong positive correlation with pH, the number of Bacillus spp. and number of Clostridium spp. In contrast, Vibrio spp. number was strongly negative correlated with water salinity (r2 = 0.632, p < 0.05). Salmonella species were detected only 2 area around shrimp farm in between December of a year-round. In this study area, there are no evidence that the number of Salmonella and Clostridium species founded related to changing of season. This is the first baseline data as an alternative guide concept for the determination of bacterial indicators. Pathogenic bacteria number can be applied to be a key factors for a rapid health assessment for villager around study area that related to EIA in the near future. HIGHLIGHTS The common problem in biomonitoring process in environment are limit of biological indicator and less data collected to establish relative between bioindicator and environmental parameters Key pathogenic bacteria groups were selected and analyzed conducted in order to find the rapid-read method for biomonitoring and assessment This is the first baseline data as an alternative guide concept for the determination of bacterial indicators. Pathogenic bacteria number can be applied to be a key factors for a rapid health assessment for villager around study area that related to EIA in the near future GRAPHICAL ABSTRACT